Praktik E-Voting Muktamar Muhammadiyah ke-48: Pendalaman Demokrasi dan Refleksi Etika Politik Islam (POLITEA, 2023)
This paper wants to reveal the contestation of power in Islamic mass organizations. The contestation for power that usually runs hot turns out to be cold and shady in the Muhammadiyah organization. This progressive Islamic movement uses the e-voting system in its election process. This process started with the selection of 216 leadership candidates, then narrowed down to 126 prospective candidates, 92 prospective candidates, up to 39 candidates and ended with 13 leadership. The tiered selection process from the tanwir meeting until the 13 leaders were elected was carried out through e-voting. There are several advantages of this e-voting system, it is more practical and more time and energy efficient. The e-voting process is also a process of deepening and maturing democracy in the future. Where there are no prominent factions, there are no SARA issues and there is no money politics. Furthermore, if we reflect according to Islamic political ethics, the correct practice of the Muhammadiyah Conference is. How can the values of al is, al musawah, al amanah, al musulliyah and al hurriyah be applied to all the organizing committee, participants and cheerleaders of the Muktamar Muhammadiyah, to become an added value for this Islamic mass organization. The research method we used to compile this research is a qualitative method with a case study type. The practical recommendations that we provide include that the neatly arranged system in Muhammadiyah Ormas can be implemented by other mass organizations or groups. As for theoretical recommendations, namely the need to make a standard approach related to the ideal concept of e-voting,